DEVISING A GUIDE TO THE FLOWERING WINDOW OF COMMON AND INTRODUCTION VARIETIES OF BREAD WHEAT (TRITICUM AESTIVUM L.) IN IRAQ - Ary Sulayman AL -Barwary; Abdullsattar Asmair Alrijabo (European Journal of Agricultural and Rural Education, 2022)
This study was conducted in 2019/2020 agricultural season in a high rainfall area in the Fayda sub-district, Dohuk governorate .The study included two factors; the 1st factor was 64 bread wheat varieties grown in Iraq, while the 2nd factor was the sowing date in two levels: early sowing before the fall of first heavy effective rain and late sowing after the fall of the first heavy effective rain. The interaction between sowing dates and studied varieties and its effect on the flowering window was studied by determining three basic growth stages according to the Zadoks scale, which were the end of booting stage (Z-49) when first awns visible, the beginning of anthesis growth stage (Z-61), and anthesis complete growth stage (Z-69). The most important results obtained in the field study on the effect of varieties and sowing dates in the flowering window, success to develop a guide for the ideal sowing dates for bread wheat varieties in Iraq by knowing the extent to which the productivity of these varieties is affected by sowing dates, and through that it was possible to classify them into three groups, the first group of varieties can planted before the first effective rain fall , the second after the first effective rain fall, and the third is neutral, and these results were according to early and late flowering based on the LSD values of the average varieties for the three growth stages under study .